Про український конституціоналізм і його розвиток у період відновлення незалежності України - Матат, Андрій Володимирович (Київський національний університет імені Тараса Шевченка, 2021)
Розглянуто питання українського конституціоналізму в період відновлення незалежності України. Досліджено юридичний процес проголошення незалежності в Україні, а також пов'язані з ним події, як-то ухвалення Конституції України – Основного закону держави. Крім того, аналізується категорія "конституціоналізм" як універсальне поняття в конституційному право, його змістовне наповнення цінностями та принципами. Указані особливості мають свою специфіку в межах окремої демократії, адже на прикладі дослідження українського конституціоналізму автор звертається до поняття "незалежність" як конституційно закріпленої характеристики держави. З'ясовано, що конституціоналізм в Україні має тісний зв'язок з європейською моделлю, а також характеризується власною специфікою, до якої належить незалежність як конституційна цінність і конституційний принцип. Указані обставини автор пояснює тим, що на конституційному рівні серед загальних засад конституційного ладу закріплено незалежність у переліку ознак держави за статтею 1 Конституції України. Окремо розглянуто доктринальні положення, присвячені дослідженню конституціоналізму українськими правниками, а також аналізується рішення Конституційного Суду України, в якому розкрито значення України як незалежної держави. Таким чином автор пояснює специфіку українського конституціоналізму.

The paper deals with the study of Ukrainian constitutionalism and its development during the restoration of Ukraine's independence. The category of "constitutionalism" is a topical issue in legal doctrine, and it is analysed concerning various aspects in constitutional law and the theory and history of law. Constitutionalism is a universal concept that contains the basic principles and values, but a certain specificity of this term has its own feature regarding the example of a particular state. That is why the category of "constitutionalism" is an actual topic. The article aims to examine constitutionalism and its features in Ukrainian legal system. The author places special emphasis on the period of restoration of Ukraine's independence. The independence of Ukraine influences the peculiarities of the development of Ukrainian constitutionalism, which derives from the European model of constitutionalism. The Constitution of Ukraine is an important object of analysis of the specifics of Ukrainian constitutionalism. The author determines that the Constitution of Ukraine enshrines independence as the basis of the constitutional order. Article 1 of the Constitution of Ukraine states that Ukraine is an independent state and the Constitutional Court of Ukraine's practice reveals the essence of independence as a constitutional value and a constitutional principle. The author uses systematic, structural, and comparative legal methods as a complex approach to obtaining the results of the research. Finally, the research contains the conclusions that enable the author to provoke the motivation for studying the outlined topic in other scientific works. The paper aims at contributing to the growing research highlighting the current issues of Ukrainian constitutionalism.
On Ukrainian constitutionalism and its development during the restoration of Ukraine's independence
Keywords: конституціоналізм; український конституціоналізм; незалежність; відновлення незалежності України; Конституція України; constitutionalism; Ukrainian constitutionalism; independence; restoration of independence of Ukraine; Constitution of Ukraine